Measuring financial stress and economic sensitivity in CEE countries - Maciej Krzak; Grzegorz Poniatowski; Katarzyna Wąsik (Center for Social and Economic Research (CASE), 2014)
This report presents the methodology for the construction of the Financial Stress Index (FSI) and the Economic Sensitivity Index (ESI) and investigates the economic situation in twelve Central and East European Countries (CEECs) between 2001 and 2012. The objective of this paper is to capture key features of financial and economic vulnerability and examine the co-movement of economic turmoil and financial disturbances that strongly affected the CEECs in the last decade. Our main finding is that the FSI can be used as a leading indicator and can be used to recognize changing trends in the index. A shift in the value of the index proves that EU accession has a positive, but minor influence on financial stability in the CEECs. On the other hand, the impact of the introduction of the euro in Estonia, Slovakia and Slovenia is ambiguous. For most of the countries in our sample, in 2007, the FSI started to grow rapidly, reaching its peak around the third quarter of 2008. Consequently, financial stress remained high for a few quarters and started to fall gradually. For a number of countries, we observe higher financial stress in the latest period of our analysis, i.e. 2010-2012. However, the value of the FSI was significantly lower than three years earlier. The results show that indices might be helpful in predicting future recessions. However, forecasting properties seem to be limited at this stage of our work.
Keywords: G01; E32; C43; 330; financial stress; economic sensitivity; economic indicators; Central and Eastern Europe